Healthcare professionals' perceptions of digital health competence: A qualitative descriptive study - Erika Jarva; Anne Oikarinen; Janicke Andersson; Anna‐Maria Tuomikoski; Maria Kääriäinen; Merja Meriläinen; Kristina Mikkonen (Wiley, 2022)
Abstract Aims and objectives This study aims to provide insight into healthcare professionals' lived experiences of digital health competence with the objective of improving the knowledge of how digital health competence is perceived by healthcare professionals. Background Healthcare professionals need to adjust to the digital era to provide quality and ethical care. Previous research has rarely adopted a healthcare professional's standpoint to describe their perceptions of digital health competence, even though their perspective in how new care practices are designed and implemented is vital. Design A qualitative descriptive study. Methods Healthcare professionals (nurses and allied health professionals) from versatile healthcare settings were recruited for individual semi‐structured interviews in Sweden (n = 5) and Finland (n = 15) (spring 2019‐summer 2020). Purposive and convenience sampling was used. Participants' backgrounds were in the public and private sectors. The interviews were transcribed for inductive content analysis. The SRQR guideline guided the study process. Results Healthcare professionals' perceptions of digital health competence are connected to competence to provide patient‐centric care through digital channels, using technology and digital health systems, interacting with the patient through digital means, evaluating what digital health is and combining digital and traditional methods. Professionals' perceptions of their own digital health competence were divided, with the participants either reporting sufficient competence or perceiving a lack of skills in some specific areas. Conclusions Healthcare professionals' perceptions of digital health competence focus on the ability to provide patient‐centric care by evaluating the need and possibilities for using digital health services jointly with more traditional methods. This study provides a sound basis for digital health research, but future studies should focus on elucidating factors which affect digital health competence and competence development. Relevance to clinical practice The results of this study can guide healthcare practices and digital health implementation, as well as function as a basis for instrument or theory development. Health care and nursing leaders should enable the resources to hybrid practices in patient‐centric care provision.